2020
DOI: 10.36233/0372-9311-2020-97-1-7-14
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining and Characterization of the Monoclonal Antibodies Against G-Protein of the Respiratory Syncytial Virus

Abstract: The aim of this study was to obtain hybridomas producing monoclonal antibodies (Mabs) to the G-protein of the respiratory syncytial virus (RSV), and to evaluate their immunological characteristics and virus-neutralizing activity.Material and methods. Mouse Mabs were obtained using hybridoma technology. The properties of Mabs were studied by enzyme-linked immunosorbent assay (ELISA), immunofluorescence staining (IF) of infected cells, as well as by biological neutralization test in vitro (NT). To identify epito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Despite the general principle of synthesis and homology, the enzymes AlpA and AlpB differ in how they are secreted into the environment [51]. The mAbs described in [52] bind to two different epitopes of G protein of the respiratory syncytial virus, possess a virus-neutralizing activity, demonstrate an additive effect in interaction, detect the viral antigen in infected cell cultures, and can be used to reveal the virus in clinical material by immunofluorescence assay and ELISA. Studies using mAbs have shown the significance of the C-terminal domain of hemolysin II for the hemolytic activity of Bacillus cereus (which causes infections in persons with weakened immunity and is one of the widespread causes of intra-hospital infections) [53], as well as its ability to bind to cell membranes [54] and be oligomerized in the presence of cell membranes [55].…”
Section: Monoclonal Antibodies As Tools To Study Biological Molecules and Intermolecular Interactionsmentioning
confidence: 99%
“…Despite the general principle of synthesis and homology, the enzymes AlpA and AlpB differ in how they are secreted into the environment [51]. The mAbs described in [52] bind to two different epitopes of G protein of the respiratory syncytial virus, possess a virus-neutralizing activity, demonstrate an additive effect in interaction, detect the viral antigen in infected cell cultures, and can be used to reveal the virus in clinical material by immunofluorescence assay and ELISA. Studies using mAbs have shown the significance of the C-terminal domain of hemolysin II for the hemolytic activity of Bacillus cereus (which causes infections in persons with weakened immunity and is one of the widespread causes of intra-hospital infections) [53], as well as its ability to bind to cell membranes [54] and be oligomerized in the presence of cell membranes [55].…”
Section: Monoclonal Antibodies As Tools To Study Biological Molecules and Intermolecular Interactionsmentioning
confidence: 99%
“…Эффективность паливизумаба у недоношенных детей с бронхолегочной дисплазией была подтверждена отечественными авторами в результате многоцентрового исследо-вания: у детей, которые относились к группе высокого риска тяжелого течения РСВ-инфекции по причине недоношенности, зарегистрировано снижение частоты госпитализаций после 3 инъекций паливизумаба до 0,3% [4]. Однако применение препарата не предотвращает повторного заболевания, эффективность препарата значительно ниже при лечении доношенных новорожденных и более старших детей, а более аффинные антитела к F-белку (мотавизумаб) вызывали аллергические реакции [5]. Кроме того, высокая стоимость препарата препятствует его широкому использованию.…”
Section: Introductionunclassified